Necesidad de establecer de forma expresa en el Código orgánico de organización territorial, Autonomía y descentralización la atribución del Gad para realizar el control y establecer la Suspensión motivada de los trabajos en las Concesiones mineras cuando éstas no observen Lo establecido en las concesiones y atenten al Manejo sustentable de los recursos naturales y Al medio ambiente - Mogrovejo Morocho, Julio Cesar (2014)
Pathetic and wise expression of that great statesman Franklin D. Roosevelt and the current bring up this thought that back in the January 1982 - April 1945 was 4 times expressed by the President of the United States. That was so far producing reflection analysis Kyoto protocols , Rio de Janeiro and other conferences on the environment , conferences have led to a profound reflection : The inescapable need to save the Planet Earth. There is a phrase : If you're part of the problem , you're part of the solution , therefore, feeling part of the problem , as part of the planet earth , we are part of the solution and we must bring to our efforts to improve the existing legislation each of the countries on the conservation of the environment through rational and sustainable exploitation of existing in each of the countries that make up the cluster from non -renewable natural resources. Particularly Ecuador has made great strides in the Mining and Environmental legislation , but it is necessary that the community feels active part of the control, conservation and sustainable management of the resources that nature has generously placed in the territory of our Republic . Only the involvement of people trafficking and conflict resolution is a thermometer that lets us know the degree of civic maturity of the inhabitants of a region. Much has been made of the REVOLUTION CITIZEN, it is nothing but the result of maturity Citizens demonstrating against the problems of their environment. Logically that maturity involves a thorough analysis with knowledge of cause and effect and making more accurate decisions regarding the case in question, according to the prevailing legal framework in the environment. Therefore, natura Foundation takes that phrase makes us think and we regresses , then, is not our nature , we must understand that the return and A nation that destroys its soil destroys itself. Forests are the lungs of the earth , purify the air and give sheer force our people " Franklin D. Roosevelt refund demands equal or better condition than we received when we delivered it " The land is not inherited from our parents, but borrow it from our children" American Indian thought Therefore, I consider it necessary to refer a proposed Law Reform the current Organic Law on Territorial Organization , Autonomy and Decentralization , in which " NEED FOR EXPRESS determined IN ORGANIC CODE OF TERRITORIAL , AUTONOMY ORGANIZATION AND Decentralization LA GAD ATTRIBUTION TO MAKE THE CONTROL AND ESTABLISH THE SUSPENSION OF WORK MOTIVATED MINING CONCESSIONS IN WHEN THEY DO NOT FOLLOW THE PROVISIONS OF THE CONCESSIONS AND SUSTAINABLE MANAGEMENT violate OF NATURAL RESOURCES AND THE ENVIRONMENT